“Productivity and economic growth: the case of Chile” - Beyer, Harald (2001)
“The effects of business cycles on growth”, Argumento planteado, “Coping with Chile´s external vulnerability: a financial problem”, Relación entre mercados accionarios, bancos y crecimiento.